Transforming grey to green: Enhancing microclimates in hot arid regions with green open spaces - Hmoud, Saad Mohsin; Ibrahim, Hamsa Abdelrahman; Hasan, Susan Abed (Edelweiss Applied Science and Technology, 2025)
The utilization of parking lots, rubbish dumps, and other similar sites has led to an increase in the number of gray spaces in urban areas over the past several years. As a means of contributing to the improvement of the urban climate and ecology, it is necessary to propose solutions for these waste regions. The purpose of this study was to evaluate the impact that converting gray spaces into green spaces has on the microclimate and thermal comfort in an open environment associated with a hot and dry climate. Baghdad’s Abu Nawas neighborhood was chosen as the location for one of the substreets that overlook Al-Saadoun Street. This neighborhood is characterized by its gray open space. A simulation technique that utilizes the program ENVI-met was employed to produce a green open space. Several factors, including air temperature, average radiant temperature, wind speed, and humidity, are included in the measurement of the microclimate factor. The findings demonstrated that greening open spaces has a positive impact on all microclimate characteristics, reduces the effects of urban heat islands, and makes these locations more sustainable and habitable overall. Additionally, the findings provide guidelines for legislators and urban planners to implement these improvements in regions that are hot and dry.